Chemotherapy of colorectal liver metastases induces a rapid rise in intermediate blood monocytes which predicts treatment response. (2nd June 2016) - Schauer, Dominic; Starlinger, Patrick; Alidzanovic, Lejla; Zajc, Philipp; Maier, Thomas; Feldman, Alexandra; Padickakudy, Robin; Buchberger, Elisabeth; Elleder, Vanessa; Spittler, Andreas; Stift, Judith; Pop, Lorand; et al.
ABSTRACT: We have previously reported that intermediate monocytes (CD14 ++ /CD16 + ) were increased in colorectal cancer (CRC) patients, while the subset of pro-angiogenic TIE2-expressing monocytes (TEMs) was not significantly elevated. This study was designed to evaluate changes in frequency and function of intermediate monocytes and TEMs during chemotherapy and anti-angiogenic cancer treatment and their relation to treatment response. Monocyte populations were determined by flow cytometry in 60 metastasized CRC (mCRC) patients who received neoadjuvant chemotherapy with or without bevacizumab. Blood samples were taken before treatment, after two therapy cycles, at the end of neoadjuvant therapy and immediately before surgical resection of liver metastases. Neoadjuvant treatment resulted in a significant increase in circulating intermediate monocytes which was most pronounced after two cycles and positively predicted tumor response (AUC = 0.875, p = 0.005). With a cut-off value set to 1% intermediate monocytes of leukocytes, this parameter showed a predictive sensitivity and specificity of 75% and 88%. Anti-angiogenic therapy with bevacizumab had no impact on monocyte populations including TEMs. In 15 patients and six healthy controls, the gene expression profile and the migratory behavior of monocyte subsets was evaluated. The profile of intermediate monocytes suggested functions in antigen presentation, inflammatory cytokine production, chemotaxis and was remarkably stable during chemotherapy. Intermediate monocytes showed a preferential migratory response to tumor-derived signals in vitro and correlated with the level of CD14 + /CD16 + monocytic infiltrates in the resected tumor tissue. In conclusion, the rapid rise of intermediate monocytes during chemotherapy may offer a simple marker for response prediction and a timely change in regimen.